The Effect of Using the Quizizz Application to Improve Learning Achievement of Informatics Students - Firmanda, Anggia; Yulifda Elin Yuspita; Misdar (SMART : Jurnal Teknologi Informasi dan Komputer, 2024)
Technological advances have succeeded in producing significant transformations in the educational structure, creating changes in the way students learn, their thinking patterns and creative abilities. One thing that attracts attention is the use of technology in learning, including the use of media and applications in informatics learning. This research aims to evaluate the extent to which the Quizizz application influences student learning outcomes in class XI SMAN 1 Candung. This research uses a quantitative approach with experimental methods. The research design used was Pre-Experimental with One-Group Pretest-Posttest Design. The experimental class in this research consisted of class XI fase F students at SMAN 1 Candung. The Quizizz application is used as a tool to evaluate student learning outcomes after each lesson. The research results showed that in the first test, the average pretest score was 58.81 and the posttest score was 85.05 and in the second test, the pretest average was 59.43 with a posttest score of 87.52. Utilizing the Quizizz application can improve the learning outcomes of class XI students at SMAN 1 Candung in the Informatics subject. These findings have an important impact on our understanding of how Quizizz is used as a learning tool in schools.